Self-Development Needs of Commercial Bank Employees in Luang Prabang Province - Saleumsak, Phongsawat; Duangvilaykeo, Thipphavanh; Sifongxay, Sangthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aims to: 1.) To study the level of self-development needs of commercial bank employees in Luang Prabang province. 2.) To compare personal factors on the self-development needs of commercial bank employees in Luang Prabang province. This is a quantitative study that used a questionnaire to collect data from a sample of 212 commercial bank employees to collect data from a sample of 212 commercial bank employees in Luang Prabang province. The questionnaire was designed from data research , ideas , theories , and related research articles to obtain information according to the objectives. Then, the data from the sample was analyzed using a sociological data analysis program that includes both descriptive and inferential statistics, as well as interpreting, explaining, and concluding the research results according to the objectives of this study. The results of the general information study of the key informants found that: most commercial bank employees are male, aged 36-45, married, hold an education level below a bachelor's degree, and have an average monthly income more than 10,000,000 kip, most are technical employees, and have 11-15 years of working experience. The results of the study on the self-development needs of commercial bank employees in Luang Prabang province found that: Overall, the level of self-development needs is at the highest level, which includes: self-learning, exchange of experiences, training, job coaching, and continuing education. The results of the study on the comparison of personal factors with the self-development needs of commercial bank employees found that: commercial bank employees in Luang Prabang province with different gender, education level, and position have different self-development needs with statistical significance at the 0.05 level. However, commercial bank employees with different age, status, income, and working time have no different self-development needs with statistical significance at the 0.05 level.